Technology ventures : from idea to enterprise - Dorf, Richard C.; Byers, Thomas (Thomas H.); Nelson, Andrew J. (New York, NY : McGraw-Hill, 2014)
For business, engineering, and science students and professionals who demand a comprehensive guide to high-growth entrepreneurship, Technology Ventures is the leading resource for analyzing opportunities and building new enterprises. Drawing on the latest academic research and practitioner insights, Technology Ventures integrates clear theoretical frameworks with action-oriented examples and exercises. Its broad perspective on "technology," including clean tech, information technology and the life sciences, ensures wide-ranging appeal to anyone with an interest in high-potential ventures. Entrepreneurship is playing a vital role in finding solutions to the huge challenges facing civilization, including health, communications, security, infrastructure, education, energy and the environment. The extensive features in this edition include: expanded coverage of customer engagement, the customer development process and the latest insights on business model design; special attention to university technology commercialization, open source innovation, and opportunities in mobile, digital health, 3D printing, and energy tech; enhanced organisation of key topics, including intellectual property, the new venture organisation, and marketing and sales; and extensive web-based resources, including syllabi and presentations, additional cases and business plans, and hundreds of videos of entrepreneurs and leaders.
Part I: Venture Opportunity and Strategy Chapter 1: The Role and Promise of Entrepreneurship Chapter 2: Opportunities Chapter 3: Vision and the Business Model Chapter 4: Comptetive Strategy Chapter 5: Innovation Strategies Part II: Concept Development and Venture Formation Chapter 6: The Business Story and Plan Chapter 7: Risk and Return Chapter 8: Creativity and Product/Service Developement Chapter 9: Marketing and Sales Chapter 10: Types of Ventures Part III: Organizations, Operations, and Intellectual Property Chapter 11: Intellectual Property Chapter 12: The New Enterprise Organization Chapter 13: Acquiring and Organizing Resources Chapter 14: Management of Operations Chapter 15: Acquisitions and Global Expansion Part IV: Financing and Leading the Enterprise Chapter 16: Profit and Harvest Chapter 17: The Financial Plan Chapter 18: Sources of Capital Chapter 19: Deal Presentations and Negotiations Chapter 20: Leading Ventures to Success
Dorf's name appears first on the earlier editions.
Keywords: Information technology; Entrepreneurship; New business enterprises